A new modeling approach for transversely oscillating square-section cylinders. (August 2018) - Liu, Y.Z.; Ma, C.M.; Li, Q.S.; Yan, B.W.; Liao, H.L.
Abstract: This paper proposes a new generalized semi-empirical model to simulate fluid–structure interaction forces experienced by a transversely oscillating square-section cylinder by a more comprehensive approach. The total fluctuating transverse aerodynamic forces determined by this new modeling approach are composed of three main unsteady excitation modules. The first component relates to the conventional fluid inertia effect; the second component represents the varying incidence angle effect, including the wavelength-changing effect of downstream wake undulation by introducing a circulation lag function; and the last one denotes the excitation effect due to the strong resonant interaction between wake undulation and Kármán vortex shedding. In addition, the new model establishment process follows the "simple-to-use" principle, so it can be applicable even when few experimental data are available. Good agreements are observed between the predictions by this model and unsteady force coefficient results taken from harmonically forced vibration experiments. Moreover, the new model developed in this study can not only simulate the interaction effects between the vortex-induced vibration (VIV) and galloping, but also retain the predictive capability for the cases of pure vortex resonance and pure galloping phenomena. Finally, some significant findings are also presented in the context of the aeroelastic instability phenomena.